منهج الصدمة في الاقتصاد الروسي ... سياسات ومؤشرات (المجلة العراقية للعلوم الاقتصادية, 2018)
This research aims at examine the non- possibility of Russian experience in the Transformation process into market economy ,and developmental aspect ,so ,at find the reasons that make this experience to fail and to benefit from it,the oritical The hypothesis of this research is that the turndown of economic Russian performance on the level of economic ,social and environmental aspects is affected by the shock approach to the transformation process into market economy.Thus ,the studying of this experience is requiring the show of historical challenges of this economy ,and analyize its implications in order to evaluate its results. In order to evaluate these result to reach the conclusions to prove the hypothesis,the study has been divided into two main sections.The first deals with the historical and trend development of economic policies in USSR.The second includes the implication of economic transformation and economic performance indicators in Russia